Rapid evolution of the intersexual genetic correlation for fitness in Drosophila melanogaster. (1st April 2016) - Collet, Julie M.; Fuentes, Sara; Hesketh, Jack; Hill, Mark S.; Innocenti, Paolo; Morrow, Edward H.; Fowler, Kevin; Reuter, Max
Abstract: Sexual antagonism (SA) arises when male and female phenotypes are under opposing selection, yet genetically correlated. Until resolved, antagonism limits evolution toward optimal sex‐specific phenotypes. Despite its importance for sex‐specific adaptation and existing theory, the dynamics of SA resolution are not well understood empirically. Here, we present data from Drosophila melanogaster, compatible with a resolution of SA. We compared two independent replicates of the "LHM " population in which SA had previously been described. Both had been maintained under identical, controlled conditions, and separated for around 200 generations. Although heritabilities of male and female fitness were similar, the intersexual genetic correlation differed significantly, being negative in one replicate (indicating SA) but close to zero in the other. Using population sequencing, we show that phenotypic differences were associated with population divergence in allele frequencies at nonrandom loci across the genome. Large frequency changes were more prevalent in the population without SA and were enriched at loci mapping to genes previously shown to have sexually antagonistic relationships between expression and fitness. Our data suggest that rapid evolution toward SA resolution has occurred in one of the populations and open avenues toward studying the genetics of SA and its resolution.